2011
DOI: 10.1097/bpo.0b013e31820fc522
|View full text |Cite
|
Sign up to set email alerts
|

Development and Initial Validation of the Assessment of Caregiver Experience With Neuromuscular Disease

Abstract: The initial validation demonstrated that ACEND is a valid, disease-specific measure to quantify experience on caregivers of children with NMD. Larger groups of patients across NMD disease type are currently being tested to strengthen validity findings. Additionally, the ACEND is now being administered before and after orthopaedic interventions to determine responsiveness, which is critical to health outcomes research. LEVEL OF EVIDENCE/RELEVANCE: IIc.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
35
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(36 citation statements)
references
References 38 publications
0
35
1
Order By: Relevance
“…A dichotomous variable was created to classify the children into two groups: those with moderate limitations in motor function (levels I-III) and those with severe limitations (levels IV-V). The GMFCS has proven to be a valid, reliable and stable classification system over time and in multiple studies (Gillick & Koppes 2010;Matsumoto et al 2011).…”
Section: Gross Motor Function Classification System (Gmfcs)mentioning
confidence: 99%
“…A dichotomous variable was created to classify the children into two groups: those with moderate limitations in motor function (levels I-III) and those with severe limitations (levels IV-V). The GMFCS has proven to be a valid, reliable and stable classification system over time and in multiple studies (Gillick & Koppes 2010;Matsumoto et al 2011).…”
Section: Gross Motor Function Classification System (Gmfcs)mentioning
confidence: 99%
“…The PEDI‐CAT is a unique, caregiver‐reported functional performance measure that has the potential to capture information about typical functional performance in the SMA population . It may offer several advantages over other person‐reported measures that are utilized currently in the pediatric neuromuscular field . Potential advantages include a larger item bank covering a wider range of ages and abilities, CAT‐based technology developed using IRT methods with standard and scaled scores, brief administration time, assistive device items, and individual item illustrations.…”
Section: Discussionmentioning
confidence: 99%
“…Responses to the expectation question range from never (1) to always (5), and responses to the satisfaction question range from extremely dissatisfied (1) to extremely satisfied (6). 19 …”
Section: Methodsmentioning
confidence: 99%
“…16 The CPCHILD has been used in previous research and has demonstrated responsiveness to change after hip and spine surgery. 17,18 ACEND is a psychometrically valid disease-specific instrument 19 used to assess the impact experienced by caregivers of children severely affected by neuromuscular disorders. It contains 41 impact items divided into two domains and seven sub-domains.…”
Section: Methodsmentioning
confidence: 99%